MANAJEMEN KONSERVASI LINGKUNGAN DI KAWASAN WISATA RANCA UPAS SEBAGAI DESTINASI PARIWISATA BERKELANJUTAN - Ginda Surya Trilestari; Lisna Anggi Putri (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
This research aims to implement effective environmental conservation management to ensure the sustainability of tourist destinations in the future. In addition, this research is also to analyze environmental conservation management practices in the Ranca Upas tourism area. Furthermore, how it can support the development of sustainable tourism. Another objective is to identify the challenges faced and provide recommendations to improve efficiency in the implementation of environmental management in the area. The background of this research is that the nature-based tourism area, Ranca Upas faces challenges in maintaining a balance between the increasing number of tourists and environmental sustainability. The problems found in the field include: 1. How is environmental conservation management in Ranca Upas currently implemented? 2. What are the main challenges faced in maintaining environmental sustainability in Ranca Upas tourist area? 3. How can tourism management contribute to supporting environmental conservation in Ranca Upas? The methods used include direct observation, interviews, and literature study. The result of this research shows that the management of environmental conservation management in Ranca Upas tourism area is running well. In addition, this research can recommend that to increase efficiency in the implementation of environmental management in the area more effectively.